DISCOVERING ANCIENT EGYPT IN MODERNITY: THE CONTRIBUTION OF AN ANTIQUARIAN, GIOVANNI BELZONI (1816-1819) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2016)
The main objective of this article is to allow a better understanding of the relationship between the British Empire and Ancient Egypt, and show the ways through which European countries – and particularly Great Britain – used the image of the Egyptian civilization to build a national identity and memory. Antiquarians who travelled to search for exotic antiquities had a very important role in this process because they left in their notes a record of their thoughts about the cultures of the places they visited and about the material culture they found there. These memories and reports circulated in Europe and were regarded as a source of knowledge, since they offered a version of the unknown “other” and reported the travelers’ interpretations of the past and present of foreign places. In this article I analyze the journal of one of these antiquarians, Giovanni Belzoni, in order to understand how his discourse may have corroborated the construction of a national identity, since he helped to form a large collection of Egyptian pieces of the British Museum, in England.